2020
DOI: 10.1096/fj.201902463rr
|View full text |Cite
|
Sign up to set email alerts
|

miR‐136‐3p targets PTEN to regulate vascularization and bone formation and ameliorates alcohol‐induced osteopenia

Abstract: Alcohol consumption is regarded as one of the leading risk factors for secondary osteopenia. Coupled angiogenesis and osteogenesis via distinct type‐H vessels orchestrates subtle biological processes of bone homeostasis. The dysfunction of angiogenesis and osteogenesis contributes to decreased bone mass during the development of osteopenia. Herein, we identified microRNA‐136‐3p was remarkedly downregulated in the mouse model of alcohol‐induced osteopenia. Following the alcohol administration, downregulated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…miR-7-5p induced osteogenic differentiation through repression of CRY2, which inhibited the expression of the CLOCK/BMAL1 complex [12]. miR-136-3p ameliorated alcohol-induced osteopenia with the concomitant restoration of bone mass and type-H vessel formation in a mouse model [13]. However, miR-451a accelerated bone loss via Bmp6 signaling during osteoporosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…miR-7-5p induced osteogenic differentiation through repression of CRY2, which inhibited the expression of the CLOCK/BMAL1 complex [12]. miR-136-3p ameliorated alcohol-induced osteopenia with the concomitant restoration of bone mass and type-H vessel formation in a mouse model [13]. However, miR-451a accelerated bone loss via Bmp6 signaling during osteoporosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the effects of alcohol on cell proliferation, differentiation, apoptosis and migration. The reduction of type-H vessels by alcohol plays an important role in alcohol-related bone loss [35]. We found that alcoholic diet inhibited proliferation and promoted aging of endothelial cells.…”
Section: Discussionmentioning
confidence: 71%
“…miR-136 exerts a protective function on neurons in a model of spinal cord ischemia injury [63]. miR-136-3p expression is also detected outside the CNS [64][65][66]. Circulating and CSF miR-136-3p levels are candidate biomarkers for both Parkinson's disease and Alzheimer's disease [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%